Displasia Fibrosa - revisão bibliográfica - Joaquim Ramalhão (2000)
Fibrous dysplasia is a non-neoplastic bone lesion of unknown etiology. It is a non-encapsulated lesion occuring mainly in young subjects, usually in the maxilla, and showing replacement of the normal bone by cellular fibrous tissue containing islands or trabeculae of metaplastic bone. Fibrous dysplasia is usually monostotic, but may occasionally be part of a polyostotic process. The polyostotic lesion may occur as part of McCune-Albright syndrome, a condition that includes skin pigmentation and endocrinopathies. Although fibrous dysplasis is self-limiting, the affected area does not return to normal, and there are in the literature descriptions of cases of sarcoma in fibrous dysplasia, with a frequency less than 1%.